Implementasi Program Daerah Pemberdayaan Gotong Royong (PDPGR) dalam Upaya Meningkatkan Kesejahteraan Masyarakat Kecamatan Taliwang Kabupaten Sumbawa Barat: Studi Kasus di Kelurahan Menala Kecamatan Taliwang Kabupaten Sumbawa Barat - Alfahrozy Alfahrozy; Suprianto Suprianto; Emi Salma (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
The Regional Program for Mutual Cooperation is the provision of space and affirmation of the direction of strengthening mutual cooperation as a value system and a way to achieve goals that are carried out voluntarily, together and please help based on enthusiasm, sincerity and earnestness to realize community employment opportunities efficiently, effectively and productively in an effort to improve the welfare of the community his research aims to find out the implementation of the gotong royong empowerment regional program in an effort to improve community welfare in Taliwang District, West Sumbawa Regency. This study uses a type of Descriptive research with a qualitative approach, conducted in Menala Village, Taliwang District, West Sumbawa Regency. Data was obtained through the process of interviews, observations and documentation. The results of this study show that the implementation of the Regional Program for Mutual Cooperation in an effort to improve the welfare of the community in Taliwang District, West Sumbawa Regency has been running according to the procedure to the maximum. The success of implementation can be measured from three elements, namely the program, the implementing organization and the program objectives. The realized program is adjusted to the needs of the community.